Optimizing Green_Time of a traffic signal controller / Nursyafiqah Ikmalhisam and Noraini Noordin - Ikmalhisam, Nursyafiqah; Noordin, Noraini (2018)
Traffic congestion is a major concern throughout the world especially in urban cities. It takes place following the rapid increase in automobile use in cities. Traffic signals play an important role at coordinating efficient movement of people and vehicles in the transport system. However, most conventional traffic signal controllers with pre-computed constant signal timing parameters or vehicle actuated control do not respond well to real-time traffic demand. The current study aimed to determine the optimal duration of green light (Green_Time) for installing a fuzzy logic signal controller (FLSC) at a three-way junction. Fuzzy logic incorporates qualitative values into the system, thus FLSC is widely proven to be efficient. The decision on Green_Time for this study was taken by importing the input variables (the number of vehicles on Arrival and on Queue) into a Matrix Laboratory (MATLAB) software. Comparative analysis between manually calculated results from the centroid method and MATLAB simulated results were found to be the same for all three intersections.